Impact of Ageism on the Social Wellbeing of Older Adults: Evidence from a Geriatric Home in Lagos, Nigeria - Emmanuel, Agbeni Kehinde; Obasi, Daniel Ebubechi; Gbadebo, Adedoyin Judith; Omolara, Atunwa Bushirah; Emuobor, Rolland Obaro; Oboite, Diana Uwaila; Omoijate, Anthonia (International Journal of Engineering and Management Research, 2024)
The paper examined the impact of ageism on social wellbeing of older adults. The main objective of the study is to evaluate the impact of ageism on the social wellbeing of older adults. These includes the impact of ageism on social connection, social support and on their social inclusion. Ageism is a very serious issue as it shown in terms of positive stereotypes or attitudes; it is most closely associated with negative stereotypes or attitudes. The study used mixed research method to analyse the opinion of participants. The data collected through structured questionnaire and interview guide were analysed with descriptive and Focus Group Discussion (FGD). The study concluded that there is significant impact of ageism on social wellbeing of older person in the society as ageism affect their social connection, support and exclusion with younger generation. Furthermore, the result to a very negative stereotype in the social connection, support and exclusion older person faces in the society. Some of these discriminations are imposed by the younger generation who feel that older adults in the society are less important and difficult to relate with. Some attitude and perceptions portrays by younger generation against older persons are offensive and discriminative. The study recommended that public education, creating opportunities for older and younger people to interact advocate for stricter policies that protect older adults from age-based discrimination in all social settings, including workplaces and public services will help to reduce the discrimination that exist in the society.